2015
DOI: 10.1016/j.ajog.2014.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Does treatment for cervical and vulvar dysplasia impact women’s sexual health?

Abstract: Human papillomavirus (HPV)-associated disease represents an immense public health burden worldwide. Persistent HPV infection can lead to the development of cervical dysplasia and vulvar dysplasia, both of which have been increasing in incidence in women in recent years. Numerous studies have focused on methods for screening and diagnosis of cervical dysplasia, but few have looked at the effects of treatment on women's psychological and sexual health. Even fewer studies have addressed these issues in women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 29 publications
0
18
0
15
Order By: Relevance
“…Javelle et al (2015), em estudo acerca dos acometimentos articulares pós-infecção (2013), ressaltam a importância da análise do SF36 pelos scores dos domínios, e desse modo, o tratamento foi capaz de melhorar a percepção do estado geral de saúde e principalmente foi motivador, haja vista a melhora na limitação por aspectos emocionais que se encontrava muito comprometida no início do tratamento.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Javelle et al (2015), em estudo acerca dos acometimentos articulares pós-infecção (2013), ressaltam a importância da análise do SF36 pelos scores dos domínios, e desse modo, o tratamento foi capaz de melhorar a percepção do estado geral de saúde e principalmente foi motivador, haja vista a melhora na limitação por aspectos emocionais que se encontrava muito comprometida no início do tratamento.…”
Section: Discussionunclassified
“…Embora, a ação contínua de humanizar encontra-se como complexa no campo da saúde, havendo dificuldade em sua implementação por meio dos profissionais, evidenciando em especial os profissionais atuantes em UTI. Por assim, alegarem a razão pela qual há essa defasagem ou até mesmo o despreparo que acontece na formação da carreira por isso, alguns profissionais demonstram-se despreparados durante a execução de uma assistência dita humanizada (PROENÇA et al, 2017 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It is shown that even the diagnosis of CIN can have many psychological effects among patients (Frederiksen et al, 2015) ,so it is presumable that treatment with LEEP can cause patients anxiety and because of the location of the lesion, the treatment may have a significant effect on the patient's sexual function and desire. The few studies that investigated the procedure's effect on sexual well-being had a limited number of patients and most of these studies used non-validated evaluation techniques (Cendejas et al, 2015) In this study, we aimed to document the impact of LEEP on female sexual function using validated modalities that can lead to identification, precautions, and treatment of the physiological and sexual effects of the procedure on women's sexual function.…”
Section: Introductionmentioning
confidence: 99%
“…Kanama, enfeksiyon, servikal stenoz gibi nadir görülen komplikasyonlar görülebilmektedir (4) . Reprodüktif çağdaki kadınlarda seksüel aktif dönemde yapılan LEEP kadın psikoseksüel fonksiyonlarını da etkileyebilmektedir (5)(6)(7)(8)(9)(10) .…”
Section: Introductionunclassified